Ta có \(2^x+\left(x^2+1\right)\left(y-2\right)\left(y-4\right)=0\)
Mà \(2^x>0,x^2+1>0\)
=> \(\left(y-2\right)\left(y-4\right)< 0\)
=> \(2< y< 4\)
=> \(y=3\)
Thay y=3 vào đề bài ta có:
\(2^x-\left(x^2+1\right)=0\)
=> \(2^x=x^2+1\)
Mà \(2^x\)chẵn với \(x>0\)
=> \(x\)lẻ
Đặt \(x=2k+1\)(k không âm)
Khi đó \(2^{2k+1}=\left(2k+1\right)^2+1\)
=> \(2.2^{2k}=4k^2+4k+2\)
=> \(2^{2k}=2k^2+2k+1\)
+ k=0 => \(2^0=1\)thỏa mãn
=> \(x=1\)
+ \(k>0\)=> \(2^k\)chẵn
Mà \(2k^2+2k+1\)lẻ với mọi k
=> không giá trị nào của k thỏa mãn
Vậy x=1,y=3